(3cGed GdUfGYI GdWHjIs - (3Ydj Hf YHGS GdeLhSj,fMh (B400 (3g`s ((3gHg Gddg Hf YHO GdLHGQ Hf GHQGgje Hf HSGe GdLHdi s)
(3ChdgG (B:s
(3GdHGH GdChd ai eOGhdI hQe GddgGg EPG YQV ddgGg GdhQe GdMGQ ajfHZi Cf JaUO UGMHgG GdbjaGd hJMd WHjYJg s
(3BNQgG (B:s
(3GdHGH GdKdGKhf ai PcQ GdJi JbWY TghI GdWjf hZjQgG ef GdTghGJ JeJ GdebGdI GdYGTQI ef GdLRA GdKGfi GdYedi s
(3Cdag GdeDda dYVO GdOhdIs
(3HgG fXGe GdJYbjHIs
(3fSNI KGfjI fSNI NRGFfjI s
(3bQf GdfSN (B:s
(3GdbQf GdSGOSs
(3GdJhKjbGJ GdeQLYjI (B:s
Keywords: (3GdWHs